IMPACT OF WATER STRESS CONDITIONS ON ASSOCIATION OF AGRO-MORPHOLOGICAL, PHYSIO-CHEMICAL AND KERNEL QUALITY-RELATED TRAITS IN MAIZE HYBRIDS - RAFIQ, M; UMER, N; KANWAL, S; SATTAR, S; ASLAM, MN; GHANI, A; IBRAR, I; MURTAZA, G; JAMIL, S; SHAHZAD, R; ABBAS, M; PARVEEN, N; et al. (Biological and Clinical Sciences Research Journal, 2024)
Changing climatic conditions, especially high temperatures and droughts are one of the major factors hindering sustainable maize production in major maize-growing areas of the world. The current study was designed to determine the association between different morphological, physiological, biochemical, and kernel quality-related traits in maize hybrids under water-deficient conditions. The experiment material was comprised of seven indigenously developed maize hybrids from Maize and Millets Research Institute, Yusafwala-Sahiwal (YH-5482, YH-5427, YH-5404, YH-1899, FH-949, YH-5577, and YH-5395), one maize hybrid developed by local seed company i.e., Kissan Seed Corporation (SB-9663) and two maize hybrids developed by multinational seed companies i.e., Corteva Seeds Pvt Ltd. (P-1543) and Syngenta Seed Pvt Ltd. (NK-8441). The experiment was executed under a randomized complete block design with four replications. The results revealed that highly significant genetic variations were present among maize hybrids for morphological, physiological, biochemical, and kernel quality traits under water-deficient conditions except for ear length for which variations were found to be non-significant. Moreover, correlation coefficient analysis depicts a strong positive correlation of kernel yield with days to 50% silking, days to 50% tasseling, stomatal conductance, transpiration rate, total chlorophyll contents, 1000-kernel weight, ear length, and plant height. However, kernel yield was found to be negatively correlated with hydrogen peroxide, superoxide dismutase, and proline contents. Similarly, path coefficient analysis showed that days to 50% silking had the highest direct positive effect on kernel yield followed by 1000-grain weight, starch contents percentage, and ear height. Therefore, parental material selection must be done using these yield-associated trades under water-deficient conditions.